The Influence of Entrepreneurial Orientation, Business Environment and Management Ability on Success MSMEs : Case Study on Women's Cooperatives Mulia Harjosari 1 Medan Amplas - Afni Suhaida; Mhd. Dani Habra; Sari Wulandari; Arief Hadian (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of entrepreneurial orientation, business environment, and management skills on the success of Micro, Small, and Medium Enterprises (MSMEs) at the Mulia Harjosari 1 Medan Amplas Women's Cooperative. The research method used is a quantitative approach with multiple linear regression analysis techniques. The population in this study was 241 people, with a sample of 70 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using the SPSS version 26 program. The results of the study showed that partially and simultaneously, the three independent variables, namely entrepreneurial orientation, business environment, and management skills, had a positive and significant effect on the success of MSMEs. The coefficient of determination (R²) value of 41.7% indicates that the model used is able to explain the variation in MSME success by 41.7%, while the rest is influenced by other variables outside the model. This finding emphasizes the importance of strengthening entrepreneurial capacity, effective managerial management, and creating a business environment that supports the growth and success of MSMEs, especially in women's cooperatives.